2010
DOI: 10.1186/1476-4598-9-215
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-glycome biomarker for monitoring development of DENA-induced hepatocellular carcinoma in rat

Abstract: BackgroundThere is a demand for serum markers for the routine assessment of the progression of liver cancer. We previously found that serum N-linked sugar chains are altered in hepatocellular carcinoma (HCC). Here, we studied glycomic alterations during development of HCC in a rat model.ResultsRat HCC was induced by the hepatocarcinogen, diethylnitrosamine (DENA). N-glycans were profiled using the DSA-FACE technique developed in our laboratory.In comparison with control rats, DENA rats showed a gradual but sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Promising candidates have been reported, including those derived from type IV collagen, 196,197 type I collagen, 198 type V collagen, 199 and type VI collagen. 200 Systemic approaches, such as global profiling of serum glycoproteins, have also been utilized, 201 and this technique is now being validated in rodent models (e.g., Fang et al, 202 Blomme et al,…”
Section: -178mentioning
confidence: 99%
“…Promising candidates have been reported, including those derived from type IV collagen, 196,197 type I collagen, 198 type V collagen, 199 and type VI collagen. 200 Systemic approaches, such as global profiling of serum glycoproteins, have also been utilized, 201 and this technique is now being validated in rodent models (e.g., Fang et al, 202 Blomme et al,…”
Section: -178mentioning
confidence: 99%
“… 5 7 One of the best documented examples of aberrant glycosylation is the progression of liver disease to hepatocellular carcinoma (HCC). 8 , 9 In the case of liver disease, changes in protein N-glycosylation can be analyzed efficiently by serologic monitoring of liver-secreted glycoproteins. 10 12 Reported changes of N-glycan repertoire in cancer include the formation of bisecting glycans with one molecule of N -acetylglucosamine attached via β1–4 bond to the branched core mannose, asialo and agalacto glycans, truncated structures with terminal galactoses or N -acetylglucosamines, (poly)- N -acetyllactosamines with beta 1–6 branching, and fucosylated glycans with fucose attached mainly at the C-3 position of outer arm N -acetylglucosamine or less frequently at the C-6 N -acetylglucosamine of the N-glycan core.…”
Section: Introductionmentioning
confidence: 99%
“…Glycoconjugates are important information-bearing biomacromolecules of the cell membrane, and abnormal expression levels of glycoconjugates in tumours have been reported (7). Previous studies with HCC patients have focused on the abnormal expression of glycoproteins (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Souady et al recently reported that CD75s-and iso-CD75s-ganglioside expression in HCC cells is associated with poor histopathological differentiation (19).…”
mentioning
confidence: 99%